159 Outcomes of Ventriculoperitoneal Shunt Placement with or without Laparoscopic Assistance: An Analysis of the National Inpatient Sample. (1st April 2022) - Zhao, Kevin; Maloney, Monica; Hilden, Patrick; Turner, Amber; Merchant, Aziz; Agarwalla, Pankaj K.
Abstract : INTRODUCTION: Ventriculoperitoneal shunt (VPS) can be placed solely by a neurosurgeon often via an open-laparotomy approach, or laparoscopically as a collaborative effort between a neurosurgeon and a general surgeon. Prior studies have shown conflicting results when examining outcomes regarding infection, revision rate, hospital charges, length of stay, and mortality between the open mini-laparotomy and the laparoscopic approaches. METHODS: We performed a retrospective database study of the NIS from October 2015-December 2017 utilizing International Classification of Diseases, 10th Revision coding to identify all cases of VPS placement. All analyses accounted for the sampling design of the NIS. RESULTS: A total of 6, 580 cases (4, 969 with open mini-laparotomy approach and 1, 611 with laparoscopic collaborative approach) met inclusion criteria. Hospital charges (median 91, 900 v. 84, 400; p = 0.231) and revision rate (3.2% v. 3.1%; p = 0.796) were similar between approaches. There were no significant differences in length of stay, mortality, or complication rates between the two approaches. CONCLUSION: The collaborative, laparoscopic approach to VPS placement has similar outcomes and is non-inferior to the traditional open mini-laparotomy approach.